Gambaran Perilaku Perawatan Kaki dan Nilai Abi Pada Penderita Diabetes Mellitus di Puskesmas Gambirsari - Vindy Ramdani; Mulyaningsih (Galen: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Background: Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by hyperglycmia, which increases the risk of diabetic foot ulcers due to suboptimal foot care. Objective: This study aims to describe foot care behaviors and ABI values among patient at Gambirsari Health Center. Method: This Descriptive Quantitative study employed accidental sampling with 81 DM patient at Gambirsari Health Center. Data were collected using the validated and reliable NAFF questionnaire for foot care behavior and ABI measurements via tensiometer, followed by univariate analysis. Results: Most respondents were aged 40-59 years (69,1%), female (80.2%), had high school education (37.0%) and had suffered DM for 1-5 years (82.7%). Foot care behavior was poor in (66.7%), while ABI values were normal (64.2). Conclusion: Although foot care behavior is poor among most DM patients at GAmbirsari Health Center. ABI values are predominantly normal. Routine education is therefore essential for preventing diabetic foot ulcers.